IMPROVING STUDENTS' VOCABULARY KNOWLEDGE THROUGH RACE TO THE BOARD GAME FOR ESP (ENGLISH FOR SPECIFIC PURPOSES) - Chusnul Chotimah; Tauricha Astiyandha (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
The importance of vocabulary learning to knowledge English language and cannot be denied. Vocabulary is one of crucial parts to be mastered if someone wants to communicate in English precisely. In line with it, one of the medias used in EFL Classroom to learn vocabulary of English is Race to The Board for ESP. The purpose of this research was to improve students’ vocabulary knowledge by using Race to the Board game for ESP in the Class XI accounting students of SMK Hutama. The method used in this research was Classroom Action Research which consists of Planning, Acting, Observing, and Reflecting. The participants of this research were the eleventh-grade accounting students at SMK Hutama consist of 32 students. The result of this research showed that using Run to the Board Language Games for ESP can be very effective and useful in facilitating the teaching or learning of English vocabulary for the students.